The orchid house - 20160731 frey50 (New York Atria, 2011)
Spanning from the 1930s to the present day, from the Wharton Park estate in England to Thailand, this sweeping novel tells the tale of a concert pianist and the aristocratic Crawford secrets are revealed, leading to devastating consequences.
Keywords: 1930s; Family secrets; World War II